Public Reporting and Pay-for-Performance: Safety-Net Hospital Executives' Concerns and Policy Suggestions - L. Elizabeth Goldman; Stuart Henderson; Daniel P. Dohan; Jason A. Talavera; R. Adams Dudley (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2007)
Safety-net hospitals (SNHs) may gain little financial benefit from the rapidly spreading adoption of public reporting and pay-for-performance, but may feel compelled to participate (and bear the costs of data collection) to meet public expectations of transparency and accountability. To better understand the concerns that SNH administrators have regarding public reporting and pay-for-performance, we interviewed 37 executives at randomly selected California SNHs. The main concerns noted by SNH executives were that human and financial resource constraints made it difficult for SNHs to accurately measure their performance. Additionally, some executives felt that market-driven public reporting and pay-for-performance may focus on clinical areas and incentive structures that may not be high-priority clinical areas for SNHs. Executives at SNHs suggested several policy responses to these concerns—such as offering training programs for SNH data collectors—that could be relatively inexpensive and might improve the cost-benefit ratio of public reporting and pay-for-performance programs.